2018
DOI: 10.3389/fpls.2018.00360
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lipid Markers of Plasmopara viticola Infection in Grapevine Using a Non-targeted Metabolomic Approach

Abstract: The Oomycete Plasmopara viticola is responsible for downy mildew, which is one of the most damaging grapevine diseases. Due to the strictly biotrophic way of life of P. viticola, its metabolome is relatively poorly characterized. In this work, we have used a mass spectrometry-based non-targeted metabolomic approach to identify potential Plasmopara-specific metabolites. This has led to the characterization and structural elucidation of compounds belonging to three families of atypical lipids, which are not dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…It has been reported that grapevine lacks a P. viticola-specific recognition system (Gaspero, Cipriani, Adam-Blondon, & Testolin, 2007) and that an activation of a successful inducible defence mechanism cannot occur (Legay et al, 2011;Ma et al, 2018;Perazzolli et al, 2012;Polesani et al, 2008;Su et al, 2018;Vannozzi, Dry, Fasoli, Zenoni, & Lucchin, 2012). According to Chitarrini et al (2017), Nascimento et al (2019) and Negrel et al (2018), specified metabolites seem to be associated with the defence response.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that grapevine lacks a P. viticola-specific recognition system (Gaspero, Cipriani, Adam-Blondon, & Testolin, 2007) and that an activation of a successful inducible defence mechanism cannot occur (Legay et al, 2011;Ma et al, 2018;Perazzolli et al, 2012;Polesani et al, 2008;Su et al, 2018;Vannozzi, Dry, Fasoli, Zenoni, & Lucchin, 2012). According to Chitarrini et al (2017), Nascimento et al (2019) and Negrel et al (2018), specified metabolites seem to be associated with the defence response.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore used a fatty acid methyl esters (FAMEs) analysis to quantify the oomycete in plant tissues. P. infestans produces specific fatty acids, such as the eicosapentaenoic acid (EPA; C20:5) 27,28 that may serve as molecular markers to quantify the oomycete biomass in plant tissues, as previously demonstrated for P. sojae or Plasmopara viticola 29,30 . FAME analysis of inoculated leaf discs revealed several fatty acids that were specifically detected in heavily infested samples (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Five long-chain polyunsaturated FAs (ARA/C20:4n6, ETA1/C20:3n6, ETA2/C20:3n6, EPA/C20:5n3, and DHA/C22:6n3) and two odd-chain FAs (cisPDA/C15:1n5 and cisHDA/C17:1n7) were detected and included in the analyses. Since Esca-associated fungi have never been detected in the leaves [ 33 , 37 ], these compounds could have been produced by other grapevine pathogens [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it was shown that lipid signaling events play an important role in the resistance of grapevine to the biotrophic oomycete Plasmopara viticola (causal agent of downy mildew), through changes in α-linolenic acid (ALA) levels, JA biosynthesis, and phospholipase A activity in leaves [ 7 , 9 ]. Ceramides and derivatives of arachidonic (ARA) and eicosapentaenoic acids produced by P. viticola sporangia were detected in diseased tissues at the very early stages of the infection process, but not in healthy tissues [ 24 ]. Besides downy mildew, V. vinifera is prone to several other economically damaging diseases, such as grapevine trunk diseases (GTDs).…”
Section: Introductionmentioning
confidence: 99%